Reversal learning deficits during sleep deprivation: investigating the role of information acquisition failures. (2nd October 2020) - Lawrence-Sidebottom, Darian; Hinson, John M.; Whitney, Paul; Van Dongen, Hans P. A.; Honn, Kimberly A.
ABSTRACT: Besides degrading vigilant attention, total sleep deprivation (TSD) impairs reversal learning performance and blunts affective reactions to feedback. Whether these effects are downstream consequences of information acquisition failures from degraded vigilant attention, or distinct from degraded vigilant attention, is unclear. In well-rested individuals we simulated information acquisition failures by masking a portion of trial information in a go/no-go reversal learning task with four conditions: stimulus masking, feedback masking, alternating stimulus/feedback masking, and no-masking control. No condition reproduced the previously documented pattern of TSD effects, suggesting that information acquisition failures cannot fully account for impaired reversal learning and blunted affective reactions during TSD.